HILANG PANAS ALAMIAH MANIFESTASI PANAS BUMI DI DAERAH MINAHASA SULAWESI UTARA - Satyano Mongan (Jurnal FisTa : Fisika dan Terapannya, 2020)
The area of Minahasa ​​North Sulawesi has potential subsurface geothermal resources. This is evidenced by the appearance of geothermal manifestations on the surface which are scattered in many places. According to the law of energy balance, the heat stored in a reservoir is equal to the heat that escapes to the surface through the discharge area. Therefore, to estimate the amount of heat stored in the geothermal reservoir below the surface, measurement and calculation of the amount of heat that naturally comes out of the surface will be carried out. This study aims to determine the amount of natural heat loss from geothermal manifestations in the Minahasa area, especially in Leilem Village and its surroundings, as well as to determine the amount of geothermal speculative resources below the surface. The method used is a combination of geological and geochemical methods with measurement of physical parameters in the geothermal manifestation. The results showed that the total natural heat loss of geothermal manifestations in Minahasa Regency, especially in Leilem Village, Sonder District was 684,399 KW, while the large speculative resources of the geothermal potential were 6843.99 KW or 6.84 MW.